DESCRIPTION OF PROTEINS AND POISONS CONTAINED IN FLOUR PRODUCED FROM WHEAT GRAIN PRODUCED IN OUR REPUBLIC - Voqqosov, Zuxriddin; Khodzhiev , Ma'ruf (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: This article describes the proteins and starches contained in flour produced from wheat grains grown in our republic. Nowadays, it is important to have information about the amount and structure of wheat flour proteins in the production and processing process. In our experiments, attention is focused on these factors, i.e. methods of determining proteins in flour and information about proteins in flour products available in our republic.